Weighted Hardy–Rellich Inequality for Dunkl Operators - Jielin Lyu; Yongyang Jin; Shoufeng Shen; Li Tang (Mathematics, 2023)
In this paper, we proved a weighted Hardy–Rellich inequality for Dunkl operators based on the spherical h-harmonic decomposition theory of Dunkl operators. Moreover, we obtained the explicit constant of the inequalities, which is optimal in some cases. Our results extend some known inequalities.